Dampak Pelatihan dan Pengembangan Terhadap Kinerja Organisasi pada Bank Sulselbar Mamuju Tengah - Karmila Karmila; Andi Batary Citta; Hernita Hernita (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Globalization and technological advancements require the banking sector to maintain high-quality human resources to remain competitive. Bank Sulselbar Mamuju Tengah Branch has experienced a decline in organizational performance over the past five years, which is suspected to be influenced by inadequate training design, limited on-the-job training, and ineffective delivery styles in employee development programs. This study aims to examine the effects of training design, on-the-job training, and delivery style on organizational performance through the mediating role of training and development at Bank Sulselbar Mamuju Tengah Branch. A quantitative approach was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were collected through questionnaires distributed to 100 permanent and contract employees, and analyzed using SmartPLS software. The findings indicate that training design, on-the-job training, and delivery style significantly affect both training and development, as well as organizational performance. Moreover, training and development play a mediating role in strengthening the relationship between independent variables and organizational performance. Training and development are crucial in enhancing organizational performance. Therefore, the management of Bank Sulselbar is recommended to improve structured training design, increase the implementation of on-the-job training, and adopt more interactive and employee-centered delivery styles.